Categorization for occasioned semantics: Reanalysis of a Japanese Yamagata 119 emergency call. (October 2019) - Hayashi, Reiko
Without making any reference to traditional linguistic disciplines such as presupposition, implicature and indirect speech acts, this article analyzes how and what implicit meanings were constructed, structured and negotiated through an ambulance request call to the119 call center in Yamagata, Japan in 2011, while enhancing the cogency of the empirical approach independent from analytical theories. Through the occasioned taxonomic analysis of the occasioned semantics of the caller and the call-taker regarding the dispatch, the analysis captured definitive evidence on how a negative response was created from the call-taker's categorization process. It reveals the process in which the rejection was determined from the talk by the call-taker that was oriented toward and constructed by the conceptual knowledge of motion, which was formulated as 'walk'. A three-part-list structure was created, which formulated 'emesis' into the category of a symptom, but not into that of an illness. The analysis reports that the call-taker's method of occasioned semantics was operative and systematically patterned. Based on the results of the analysis, with linguistic evidence, the article critically argues that the rejection of an ambulance request was due in large part to the call-taker's method of categorization when asking questions, which provides an alternative account to that of a previously reported analysis.